PRIMARY MASTITIS TUBERCULOSIS CLINICALLY MIMICKING FIBROADENOMA MAMMAE - Kristin Purnama Dewi (Faculty of Medicine Universitas Kristen Duta Wacana, 2018)
Introduction: Breast tuberculosis (mastitis TB) is a rare extrapulmonary presentation of tuberculosis that marked pathologily with involvement extensively mamma lobules, which because of infection of Mycobacterium tuberculosis. Many epidemiology studies stated that the incidence of mastitis TB is more common in developing countries than developed countries. Mastitis TB occurs mainly in reproductive woman. Case: A 32-year-old woman came to Surgery Department with chief complaint right upper quadrant palpable breast lump for 4 months. Mammae dextra physical examination confirmed single nodule, size ± 3cm x 3cm x 2.5cm in superior quadrant, mobile, tender, well defined shape, feel like marble, reddish skin, warm, no skin retraction and no nipple discharge. VAS score 2. Mammosonogram was performed and indicated mastitis in the superior quadrant of mammae dextra. Fine needle aspiration revealed negative malignant cells and granulomatous with suppurative inflammation. The histopathological evaluation from mammae excision confirmed datia langhans cells and indicated granulomatous mastitis. Then patient referred to the Pulmonary Department. On TB pulmonary examination confirmed normal chest x-ray and negative acid fast basil (AFB). Patient was diagnosed with primary mastitis TB. Patient was treated with anti-tuberculosis drug (OAT) and gave good response and no side effects. Discussion: Based on the International Standards for Tuberculosis Care (ISTC) diagnosis of mastitis TB can be confirm by anamnesis, physical examination, and also some additional diagnostic test such as sonomammographic imaging, fine needle aspiration or surgical specimens for pathology examination and culture or AFB with Ziehl-Neelsen staining. In Indonesian National Guidelines for TB Control, mastitis TB was treated with fixed drug combination (FDC), intensive phase in 2 months using 4 FDC and advanced phase in 4 months using 2 FDC. In case followed up in 2 months, patient recovered very well and advised to continue the treatment. Conclusions: TB mastitis is rare even in countries with TB endemic. Diagnosis of primary mastitis TB based on clinical, radiological, pathological and microbiological. Treatment of mastitis TB with FDC for 6 months consists of an intensive phase and an advanced phase in this patient gave good outcome. Keywords: Mastitis tuberculosis, diagnosis, treatment.